Ethnopolitical Trends of Party Building in Kazakhstan and China - Lulu Wang; N. P. Kalashnikova (Евразийская интеграция: экономика, право, политика, 2024)
The role of political parties in multi-ethnic states is quite complex, as they should be focused not only on political governance at the level of the state as a whole, but also on promoting national unity in interethnic relations, forming tolerant cooperation and interaction between different ethnic groups. Aim. This article aims to take the operation and development of political parties in multi-ethnic countries such as Kazakhstan and China as examples to study the role of political parties and to study cases from the practice of their activities in maintaining national stability, promoting social harmony, and protecting the interests of small ethnic groups.Tasks. One of the tasks of political parties in multi-ethnic states is to integrate different social interests and ensure that all ethnic groups have a voice and are represented in the decision-making process at the national level.Methods. Comparative analysis is used to compare models of multi-ethnic governance in different countries or regions, and to analyze the role and effectiveness of different political parties in these models. This will help to understand the strengths and weaknesses of different governance models and identify best practices. It also analyzes the reasons for the successes and failures of different countries and political parties by analyzing their historical practices of multi-ethnic governance. This will help to understand how political parties have responded to ethnic conflicts and governance challenges throughout history.Results. The research paper pointed out that the policies developed and implemented by political parties in multicultural countries in support of the cultures of different ethnic groups, the protection and promotion of the languages, religions, traditions and cultural identities of different ethnic groups, comply with the UN standards and principles on these issues. However, as shown by the political and SWOT analysis of the statutory and program documents of the political parties in the countries studied, there are problems.Conclusion. Certainly, political parties are making efforts to ensure equal opportunities and access for all ethnic groups to the economy, education, employment and so on, in order to promote the creation of a fair and inclusive society, while ensuring the civil rights of minority ethnic groups, or as it is called in international legal literature “national minorities”.